Cost-effectiveness analysis of secukinumab in ankylosing spondylitis from the Canadian perspective. (2nd January 2019) - Goeree, Ron; Chiva-Razavi, Sima; Gunda, Praveen; Jain, Minal; Jugl, Steffen M.
Abstract: Aim: To assess the cost-effectiveness of interleukin (IL)-17A inhibitor secukinumab vs the currently licensed biologic therapies in ankylosing spondylitis (AS) patients from a Canadian healthcare system perspective. Methods: A decision analytic model (semi-Markov) evaluated the cost-effectiveness of secukinumab 150 mg compared to certolizumab pegol, adalimumab, golimumab, etanercept and etanercept biosimilar, and infliximab and infliximab biosimilar in a biologic-naïve population, over 60 years of time horizon (lifetime). The Bath Ankylosing Spondylitis Disease Activity Index (BASDAI 50) response rate was used to assess treatment response at week 12. Non-responders or patients discontinuing initial-line of biologic therapy were allowed to switch to subsequent-line biologics. Model input parameters (short-term and long-term changes in BASDAI and Bath Ankylosing Spondylitis Functional Index [BASFI], withdrawal rates, adverse events, costs, resource use, utilities, and disutilities) were obtained from clinical trials, published literature, and other Canadian sources. Benefits were expressed as quality-adjusted life years (QALYs). Cost and benefits were discounted with an annual discount rate of 1.5% for all treatments. Results: In the biologic-naïve population, secukinumab 150 mg dominated all comparators, as patients treated with secukinumab 150 mg achieved the highest QALYs (16.46) at the lowest cost (CAD 533, 010) over a lifetime horizon vs comparators. In the deterministic sensitivity analysis, results were most sensitive to changes in baseline BASFI non-responders, BASDAI 50 at 3 months and discount rates. Probabilistic sensitivity analysis showed that secukinumab 150 mg demonstrated higher probability of achieving maximum net monetary benefit vs all comparators at various cost thresholds. Conclusions: This analysis demonstrates that secukinumab 150 mg is the most cost-effective treatment option for biologic-naïve AS patients compared to certolizumab pegol, adalimumab, golimumab, etanercept and etanercept biosimilar, and infliximab and infliximab biosimilar for a lifetime horizon in Canada. Treatment with secukinumab translates into substantial benefits for patients and the healthcare system.